Hidradenitis suppurativa and chromosomal abnormalities: a case report and systematic review of the literature. (9th August 2020) - Shah, Monica; Sachdeva, Muskaan; Melendez‐Gonzalez, Maria; Piguet, Vincent; Sayed, Christopher
Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory follicular disorder that involves painful nodules, abscesses, and tunnels of intertriginous sites. Although the etiology has not been fully elucidated, recent studies have highlighted its association with chromosomal abnormalities.We present a rare case of HS in a patient with Trisomy 1q;13 and systematically summarize the association between HS and chromosomal abnormalities. A search was conducted using MEDLINE and EMBASE in OVID database. Original studies reporting HS among human subjects with chromosomal abnormalities were included. Patient demographics, disease symptomology, clinical features, and treatment histories were extracted and summarized.Thirteen studies describing 428 cases met the inclusion criteria. Of the 13 articles, nine studies reported patients with HS and Down syndrome (DS), one article investigated HS and Smith–Magenis syndrome (SMS), and three articles analyzed HS and Patau syndrome (PS). While increased prevalence of HS was found in populations with DS, with suggested mechanisms involving amyloid precursor protein cleavage product, keratinocyte proliferation, and follicular plugging, the associations between HS and both SMS and PS remain inconclusive because of limited studies with small sample size.Although evidence suggests that the genetic regulation of chromosome 21 may be implicated in the association between HS and DS, this association may be confounded by additional factors that increase the risk of HS. Further research with larger sample sizes must be conducted to strengthen our understanding of the association between HS and chromosomal abnormalities.